2013
DOI: 10.1016/j.cmet.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Metabolic Implications of Regional Differences among Fat Depots

Abstract: Fat distribution is closely linked to metabolic disease risk. Distribution varies with sex, genetic background, disease state, certain drugs and hormones, development, and aging. Preadipocyte replication and differentiation, developmental gene expression, susceptibility to apoptosis and cellular senescence, vascularity, inflammatory cell infiltration, and adipokine secretion vary among depots, as do fatty-acid handling and mechanisms of enlargement with positive-energy and loss with negative-energy balance. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
483
3
25

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 564 publications
(531 citation statements)
references
References 141 publications
(237 reference statements)
20
483
3
25
Order By: Relevance
“…Supporting this view is the finding that isolated preadipocytes exhibit intrinsic differences in many functional characteristics, including proliferation, apoptosis, and adipogenesis (12). Transcriptional profiling has also identified unique regional mRNA profiles characterized by differential expression of developmental genes (13)(14)(15), some of which correlate with obesity (HOXA5, TBX15) (16) and appear to be important regulators of adipocyte development and function (SHOX2, TBX15) (17,18).…”
mentioning
confidence: 75%
“…Supporting this view is the finding that isolated preadipocytes exhibit intrinsic differences in many functional characteristics, including proliferation, apoptosis, and adipogenesis (12). Transcriptional profiling has also identified unique regional mRNA profiles characterized by differential expression of developmental genes (13)(14)(15), some of which correlate with obesity (HOXA5, TBX15) (16) and appear to be important regulators of adipocyte development and function (SHOX2, TBX15) (17,18).…”
mentioning
confidence: 75%
“…Meanwhile, evidence has shown a depot difference in the productions of inflammatory cytokines and adipokines. For example, the expressions of cytokines such as interleukin 6 (IL-6), MCP1, and adiponectin are higher in visceral fat tissue, whereas the expression of leptin is higher in subcutaneous adipose tissue (Tchkonia et al, 2013). A recent study demonstrated that gluteal subcutaneous adipose tissue (GSAT) had less inflammatory profiles than abdominal subcutaneous adipose tissue (ASAT).…”
Section: Introductionmentioning
confidence: 99%
“…Preadipocytes, also termed "adipose-derived stem cells" or "fat cell progenitors" (38), constitute 15-50% of the cells in adipose tissue and arguably are the most abundant progenitor cell type in humans (39). We first tested whether the number of senescent preadipocytes increases in adipose tissue with aging.…”
Section: Significancementioning
confidence: 99%